Baking quality, sensory properties and shelf life of bread with polyols - Bhise, Suresh (Springer India, 2014)
The polyols namely glycerol, sorbitol and mannitol were incorporated at 2, 4 and 6 % level in flour for bread making and their effect on textural properties, bread making quality and sensory acceptability of bread was studied. The effect of incorporation revealed the increased bake absorption, bread weight and decreased specific volume. The overall acceptability scores were maximum for bread prepared with glycerol at 2 % level, followed by sorbitol at 4 % level and mannitol at 4 % level. During storage of packed bread, moisture content and water activity were higher for bread prepared from polyols as compared to control and it was observed that moisture content was higher in bread packed in Polypropylene. Formation of free fatty acid content (% oleic acid) was observed to be higher in the breads stored at ambient condition and packed in Low density polyethylene packaging material. The overall acceptability of bread decreased with the increased storage period.